CLL Update Vol 3., Issue 12 - Centre for Leadership in Learning (Centre for Leadership in Learning, 2012)
Monthly e-bulletin for the Centre for Leadership in Learning.
Keywords: Workshop; Avenue to Learn Training; Course Design; Instructional Skills; Pedagogy Community of Practice Meeting; Paul R. MacPherson Teaching Fellowships; Social Justice and Critical Pedagogy Community of Practice Meeting; Accessibility Community of Practice Meeting; Level 1 Instructors Community of Practice Meeting; Community Engaged Education Community of Practice Meeting; Research on Teaching and Learning Community of Practice Meeting; Teaching Professors Community of Practice Meeting